Avaliação do impacto de atividades antrópicas no Rio Jaguaribe: o uso de hidrocarbonetos aromáticos como traçadores de fontes - Andrade, Marcia Vanessa Felix de (2012)
Polycyclic aromatic hydrocarbons (PAHs) are part of a group of compounds denominated persistent organic pollutants (POPs), which have impacted the environment. Another interesting study of PAHs is their use as molecular markers to distinguish between anthropogenic sources (pyrogenic or petrogenic) and natural (biogenic or petrogenic). Thus, this study aims for: assess the impact of human activities in the river basin Jaguaribe using PAHs as specific molecular markers, determining the concentrations of PAHs in surface sediments, their likely sources, but also evaluate how for transport and estimate the environmental risk. We chose eight points, three-influenced by fluvial predominance and five points with predominance estuarine. The sum concentration of PAHs ranged from 0.69 a 3752.02 µg.kg-1 similar to levels found in other studies considered poorly and moderately impacted. We used diagnostic ratios of PAHs to distinguish possible sources of origin of these contaminants. The reason % PER / Σ PAHs 5 rings showed that most samples there is a predominance anthropic, except for the samples PF1, PF2 and PF3 showed that natural supply. To distinguish petrogenic and pyrolytic sources used were the reasons for the low concentrations of PAHs and high molecular weight and cross diagrams of diagnostic reasons FEN/ANT x FLT/PYR and ANT/Σ (178) x FLT/Σ (202). In general, the samples (PF1, PF2 and PF3) influenced fluvial processes predominated in the samples and pyrolytic located in the estuarine area (PEs4, PES5, PES6, and PEs7 PEs8) were found petrogenic contributions. In evaluating the factors governing the transport of PAH, hierarchical cluster analysis showed a strong correlation of most of the PAHs with humic and fulvic acids, organic carbon and carbon black, both in points and in river estuaries, with a small increase the amount of related compounds in the estuary relative to river analysis. In the environmental assessment of ecological risk, in general, the sediments analyzed showed no marked toxicity levels, especially in relation to the levels of benzo (a) pyrene. Only a few samples had levels above those considered toxic and can display any potential danger to organisms.